“#PHOTOJOURNALISM” IN THE AGE OF INSTAGRAM - MOGOŞ, Andreea Alina (Studia Universitatis Babeș-Bolyai Ephemerides, 2017)
As digital technology developed over the last decades, photojournalism experienced both oportunities and threats. Thus, digital photography opened a whole range of oportunities for the press photographers: they were able to take more photos, to check instantly their quality, to briefly edit and quickly send images to the newsrooms. But, on the other hand, as the cameras and the photo gear got better and cheaper, amateur photographers started to challenge the status of professional photographers. Media organizations increasingly went on publishing user-generated-content (UGC), partly under economical pressures. Nevertheless, there were several differences between the photographic content produced by professional photo journalists and the user-generated content. Due to these diferences, even if the photo-sharing platforms allowed both professional and amateur photographers to share and promote their photos, people were more inclined to share a pro’s photo as they were user-generated content. Starting from these premises, the present paper examines several Instagram dimensions of the photojournalism concept, in order to identify who are the visual elites on Instagram and how professional networks work; which are the most proeminent photographic genres that are associated with photojournalism; and how amateur photographers behave and how they promote themselves on Instagram.